STUDI EKSPERIMENTAL GASIFIKASI UPDRAFT SEKAM PADI DAN BATUBARA UNTUK PRODUKSI GAS MAMPU BAKAR - Akhmad Syarief; Yopi Riyanto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2018)
in this research have a purpose the amount of syngas produced in the process of mixing rice husk gasification with low quality coal at temperature 500 °C and to know the number of side pruduk of Tar and Char from gasification updraft rice husk and low quality coal at temperature 500 °C. In this research, the result of syngas on updraft gasification process of rice husk and low quality coal is as much as 96,62 L. The highest volume in sempel SP 200 gr: BB 0 gr equal to 29,56 L, at sempel SP 180 gr: BB 20 gr equal to 25,7 L, at SP 140 gr: BB 60 gr equal to 21.88 L and volume at least on SP 100 gr: BB 100 gr equal to 19.45L. The result of by-product of updraft gasification of rice husk and low quality of coal was obtained by highest tar on SP 200 gr: 0 ml of 58.75 ml, at sempel SP 180 gr: BB 20 g produced as much as 45 ml, at SP 140 gr BB 60 g produced 32,5 ml and at sempel SP 100 gr: BB 100 gr yielded as much as 22,5 m